Pengaruh Kepemimpinan Transformasional Kepala Sekolah, Profesionalisme Guru, dan Peran Komite Sekolah Terhadap Peningkatan Mutu Pendidikan - Riyatno, Yuli; Kusumaningsih, Widya; Soedjono, Soedjono (PGRI Kota Semarang, 2024)
Abstract This research is motivated by the condition of the quality of public high school education in Rembang Regency which is still low. Factors that influence the low quality of public high school education in Rembang Regency are the transformational leadership of school principals, teacher professionalism, and the role of school committees. The research was carried out in Rembang Regency using a quantitative approach and ex post facto type of research. The total research sample was 199 teachers from all public high schools in Rembeng Regency. This research analysis includes simple regression analysis and multiple regression analysis. The results of the research show that: (1) there is an influence of the principal's transformational leadership on the quality of public vocational school education in Rembang Regency by 34.9% and the remaining 65.1% is influenced by other variables. The simple regression equation formed is Ŷ = 37.905 + 0.598X1; (2) there is an influence of teacher professionalism on the quality of State Vocational School education in Rembang Regency of 35.4% and the remaining 64.6% is influenced by other variables. The simple regression equation formed is Ŷ = 39.929 + 0.582X2; (3) there is an influence of the role of the school committee on the quality of State Vocational School education in Rembang Regency of 17.3% and the remaining 82.7% is influenced by other variables. The simple regression equation formed is Ŷ = 55.674 + 0.453X3; and (4) there is an influence of the principal's transformational leadership, teacher professionalism, and the role of the school committee on the quality of State Vocational School education in Rembang Regency amounting to 47.9% and the remaining 52.1% is influenced by other variables. The multiple regression equation formed is Ŷ = 12.760 + 0.342X1 + 0.391X2 + 0.128X3. Keywords: quality of education, transformational leadership of school principals, teacher professionalism, role of school committees